Kualitas Pelayanan Keselamatan Penerbangan - Datunabolon Datunabolon; Wynd Rizaldy; Djoko Priambodo (Institut Transportasi dan Logistik Trisakti, 2019)
The purpose of this study is to determine the relationship between Employee Competence (Co) and Quality of Service (Ku) with Aviation Safety (Ks). This research was conducted at PT. Jasa Angkasa Semesta Tbk. Jakarta Export warehouse with n = 45 respondents decided to keep due to saturated samples. The method analysis was simple linear regression, multiple linear regression, simple correlation and partial correlation. The results of the research are as follows; (1) there is a positive correlation between employee competency (Ko) and flight safety (Ks), (2) there is a positive correlation between service quality (Ku) and flight safety (Ks), and (3) there is a positive correlation between employee competency and quality of service towards flight safety. Based on the results of the study, the flight safety can be improved by increasing employee competence and service quality.